An Overview of Father Involvement in the Education of Children with Special Needs - Novita Maulidya Jalal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe father involvement in the education of children with special needs based on findings from previous research. This review employs a library research method by examining five scholarly articles from reputable journals that discuss the role of fathers in the educational context of children with autism, developmental delays, and hearing impairments. The analysis was conducted using content analysis techniques to identify patterns of involvement, barriers, and supporting factors influencing fathers’ roles in the education of children with special needs.The findings reveal that fathers play an essential role through two primary forms of involvement: direct involvement, such as assisting with learning activities, attending school meetings, and participating in intervention programs; and indirect involvement, including managing educational administration and coordinating with schools. Common barriers include work-related demands, limited knowledge about special needs, cultural constructions of masculinity, and the phenomenon of maternal gatekeeping. Nevertheless, father involvement has been shown to enhance children’s cognitive, socio-emotional, and academic development, as well as strengthen overall family well-being.In conclusion, father involvement is a critical component in the success of education for children with special needs, yet it still requires systemic support through parent education, inclusive policies, and improved collaboration between families and schools.